A numerical study on the effect of vibrator shape on the development of nonlinear standing waves in a 2-D acoustical resonator - Nabvai, Majid; Kamran Siddiqui, M.H.; Dargahi, Javad (Canadian Acoustics, 2007)
The numerical analysis of the effects of different shape of the vibrator on the pressure and velocity profile in 2-D nonlinear standing wave resonator is studied. The wave equation for high-amplitude nonlinear acoustic waves in a thermo-viscous fluid is derived from the basic equations of fluid mechanics along with an appropriate state equation. Three different shapes are considered for the diaphragm which are, constant shape vibrating piston, circular shape and cosine shape, to investigate the effects of the diaphragm shape on the pressure and velocity waveforms of an acoustic resonator. It is observed that for the same maximum vibrational velocity of the diaphragm, the amplitudes of the pressure and velocity for constant shape vibrating piston are largest and for cosine shape are smallest.